PENGARUH KELENGKAPAN DAN PELAYANAN TERHADAP LOYALITAS DAN RASA PERCAYA SEBAGAI VARIABEL INTERVENING (STUDI PADA DEPO PELITA SOKARAJA BANYUMAS) - Antri Yuwono; Suliyanto Suliyanto (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2011)
This research entitled, “The Influence of Products Availability and Service on Loyalty and Trust as intervening Variable". The aim of this research is to test the influence of availability, service to satisfaction, satifaction to trust, and to test trust and satisfaction to loyalty. This research was conducted in Banyumas and the objects were the customers who had visited Depo Pelita more than three times in the last six months. Based on Accidental Sampling Method, 100 customers were selected as research sample, because the exact numbers of Depo Pelita customers were not available. The method of analysis used SEM (Structural Equation Modeling) by AMOS version 4.0. The result of this research showed that availability was influential to satisfaction but service was not influential to satisfaction. Then, satisfaction was influential to trust. Eventually, satisfaction created loyalty but trust not created loyalty.